Ecotoxicological Studies on the Effect of Roundup(®) (Glyphosate Formulation) on Marine Benthic Microalgae - Sylwestrzak, Zuzanna (Int J Environ Res Public Health, 2021)
Glyphosate is a very effective herbicide and the main active ingredient in Roundup(®)—the most extensively used herbicide in the world. Since glyphosate is highly water soluble it reaches water bodies easily in surface water runoff. This prompted us to undertake an experiment to evaluate the effects of glyphosate in Roundup(®) on natural communities of marine microphytobenthos. Microphytobenthos communities were obtained from the environment, and after transporting them to the laboratory and acclimatizing them, they were tested under controlled conditions. Changes in microphytobenthos composition and structure and the deteriorating condition of the cells of community-forming organisms (assessed by analyzing changes in chloroplast shape) were used to assess the impact of Roundup(®) on endpoints. The tests indicated that microphytobenthic communities were relatively resistant to herbicide. The species richness of the communities probably enabled them to rebuild effectively. Sensitive species were replaced by those more tolerant of glyphosate. Only at the highest glyphosate concentration (8.5 g·dm(−3)) tested was a strong negative effect noted that limited community abundance and eliminated some of the organisms. The dominant diatoms in the communities were replaced by intensively developing cyanobacteria, which ultimately comprised nearly 60% of all the cells observed in the communities.